Capacidade funcional, estresse percebido e a satisfação com a vida em idosos portadores de artrose ativos e sedentários - SILVA, Murilo Augusto Martins (2022)
This paper aims to compare the level of functional capacity, perceived stress and life satisfaction in elderly people who practice physical exercises and sedentary people. Twentyseven elderly people were evaluated, 15 sedentary and 12 active, aged between 60 and 83 years. For the assessment of functional capacity, the GDLAM protocol was used, which consists of the following tests: walk 10 m, get up from a sitting position, get up from the prone position and get up from a chair and move around the house. To assess perceived stress, the Perceived Stress Scale Questionnaire was used. To assess the level of satisfaction with life, the SWLS Satisfactionwith Life Scale questionnaire. Statistical analysis was performed using the Bioestat 5.0 software, with a significance level of p<0.05. The results of the study demonstrate that physically active elderly people present better results in the tests of functional capacity performed, no significant differences were observed between the level of perceived stress and satisfaction with life in the two groups. There was also a direct correlation between the level of functional capacity of the elderly and their level of satisfaction with life.